PENGARUH FLEXIBLE WORKING ARRANGEMENT DAN PSYCHOLOGICAL WELLBEING TERHADAP KINERJA PEGAWAI DENGAN EMPLOYEE ENGAGEMENT SEBAGAI INTERVENING (Studi Pada Pegawai Dinas Kebudayaan Dan Pariwisata Kota Semarang) - Rian Anantyo; Edy Rahardja (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to examine the effect of flexible working arrangement and psychological well-being on employee engagement and employee performance. This research was conducted because there was a research gap in the form of contradictions in the results of previous research on employee performance before the COVID-19 pandemic and after the Covid-19 pandemic. That during the COVID-19 pandemic, there was demotivation from employees due to the hybrid work system and work from home. This type of research is quantitative research that uses primary data sources and secondary data. The research population is all ASN and non ASN employees of the Semarang City Culture and Tourism Office. The research sample was taken using the Census method. The data analysis technique uses SEM (Simultaneous Equaling Model) from the AMOS application. The data processing technique uses the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results of the study prove that Flexible Working Arrangements have no effect on the Performance of Semarang City Culture and Tourism Service Employees and Psychological Wellbeing has no effect on the Semarang City Culture and Tourism Office's Employee Performance; then the third hypothesis is that Flexible Working Arrangement has a significant positive effect on Employee Engagement of Culture Service Employees; and Semarang City Tourism. Psychological Wellbeing has a significant positive effect on Employee Engagement at the Semarang City Culture and Tourism Office and Employee Engagement has no effect on Employee Performance at the Semarang City Culture and Tourism Office (negatively insignificant). Keywords: flexible working arrangement; psychological well-being; employee engagement; employee performance